1999
DOI: 10.1172/jci5669
|View full text |Cite
|
Sign up to set email alerts
|

Roles of TH1 and TH2 cytokines in a murine model of allergic dermatitis

Abstract: Skin lesions in atopic dermatitis (AD) are characterized by hypertrophy of the dermis and epidermis, infiltration by T cells and eosinophils, and expression of the cytokines IL-4, IL-5, and IFN-γ. The role of these cytokines in the pathogenesis of AD is not known. We took advantage of a recently described murine model of AD elicited by epicutaneous sensitization with ovalbumin (OVA) (1) and of the availability of mice with targeted deletions of the IL-4, IL-5, and IFN-γ cytokine genes to assess the role of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
282
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(310 citation statements)
references
References 50 publications
(52 reference statements)
25
282
0
3
Order By: Relevance
“…These findings agree with previous reports that the Ag sensitization elicited the AD-like skin lesions in IgE-deficient mice (29). The thickening of the skin layer in the lesions at the OVA-sensitized site of IgE-deficient mice was similar to the skin lesions in STAT6-deficient NC mice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings agree with previous reports that the Ag sensitization elicited the AD-like skin lesions in IgE-deficient mice (29). The thickening of the skin layer in the lesions at the OVA-sensitized site of IgE-deficient mice was similar to the skin lesions in STAT6-deficient NC mice.…”
Section: Discussionsupporting
confidence: 92%
“…The infiltration of eosinophils and mast cells in STAT6-deficient NC mice was elicited in the absence of IL-4-and IL-5-producing T cells. However, this Ag-sensitized mouse model indicates the functional significance of IL-4 and IL-5 in the infiltration of eosinophils (29). These results indicate that the mechanisms regulating skin disease in NC mice differ from the Ag sensitization elicited by the AD-like skin lesions.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…6,7 In addition, the expression of not only Th2-type cytokine but also Th1-type cytokine (ie, IFN-␥ or IL-12) played a critical role in murine dermatitis and asthma models. 8,9 It has also been demonstrated that natural killer (NK) cells, like Th2 cells, play an important role in the development of allergen-induced asthma. 9 It has been suggested that antigen-presenting cells (APCs) play a crucial role in the skewing of Th1 and Th2 differentiation.…”
mentioning
confidence: 99%
“…76 On the contrary, allergen sensitized skin from mice deficient in IL-4 and IL-5 lack eosinophils and the skin from IFN-γ-deficient mice demonstrate decreased thickening of the dermis indicating the importance of Th1 and Th2 cytokines in AD. 77 Other studies have indicated the importance of Th2-cytokines, IL-4 and IL-13 at the onset of AD and IL-5 at the later stages of AD. 74 In addition to the Th1 and Th2 subset of T cells, defects in T regulatory cells have been implicated in the development of polyendocrinopathy X-linked syndrome involving hyper-IgE, food allergy, and eczema.…”
Section: Immune Mechanisms In Atopic Dermatitis a Effector Cells T Cmentioning
confidence: 98%